The Influence of Green Accounting and Sustainability Reporting Implementation on Company Value in Manufacturing Companies in the Consumer Goods Industry Sub-Sector (Listed on the IDX) - Markwok, Angeline; Susan Grace V. Nainggolan (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2024)
This study aims to determine the Influence of Green Accounting and Sustainability Reporting on Company Value. This study was conducted to show that companies that implement good Green Accounting and Sustainability Reporting reflect the Company's responsibility towards environmental and community welfare so that the Company will have the potential to increase its Company value. The method used is a quantitative approach and secondary data. A population of 54 in the Manufacturing Company in the Consumer Goods Industry Sub-Sector was taken from the Indonesia Stock Exchange website for the period 2019-2023 as many as 40 samples using the Purposive Sampling method. Data analysis and testing consist of descriptive statistics, classical assumption tests, multiple regression analysis, partial (T test) and simultaneous (F test) hypothesis testing, and determination coefficient testing. The results of this study indicate that Green Accounting have a partially significant effect on Company Value in the Manufacturing Company in the Consumer Goods Industry Sub-Sector (Listed on the IDX) with a calculated T-count value of -3.607 < T-table of 1.68595. Sustainability Reporting have not a partially significant effect on Company Value in Manufacturing Company in the Consumer Goods Industry Sub-Sector (Listed on the IDX) with a calculated T-count value of 1.544 < T-table of 1.68595. Green Accounting and Sustainability Reporting have a simultaneously significant effect on Company Value in the Manufacturing Company in the Consumer Goods Industry Sub-Sector (Listed on the IDX) with a calculated F value of 7.720 > F table 3.25 and a regression coefficient value of 29.4%.